Horizontal silicon nanowires for surface-enhanced Raman spectroscopy. (4th January 2018) - Gebavi, Hrvoje; Ristić, Davor; Baran, Nikola; Mikac, Lara; Mohaček-Grošev, Vlasta; Gotić, Marijan; Šikić, Mile; Ivanda, Mile
Abstract: The main purpose of this paper is to focus on details of the fabrication process of horizontally and vertically oriented silicon nanowires (SiNWs) substrates for the application of surface-enhanced Raman spectroscopy (SERS). The fabrication process is based on the vapor–liquid–solid method and electroless-assisted chemical etching, which, as the major benefit, resulting in the development of economical, easy-to-prepare SERS substrates. Furthermore, we examined the fabrication of Au coated Ag nanoparticles (NPs) on the SiNWs substrates in such a way as to diminish the influence of silver NPs corrosion, which, in turn, enhanced the SERS time stability, thus allowing for wider commercial applications. The substances on which high SERS sensitivity was proved are rhodamine (R6G) and 4-mercaptobenzoic acid (MBA), with the detection limits of 10 −8 M and 10 −6 M, respectively.